Peri‐prostatic adipose tissue: the metabolic microenvironment of prostate cancer. (26th March 2018) - Nassar, Zeyad D.; Aref, Adel T.; Miladinovic, Dushan; Mah, Chui Yan; Raj, Ganesh V.; Hoy, Andrew J.; Butler, Lisa M.
Abstract : Emerging data have linked certain features of clinical prostate cancer (PCa) to obesity and, more specifically, increased adiposity. Whereas the large number of clinical studies and meta‐analyses that have explored the associations between PCa and obesity have shown considerable variability, particularly in relation to prostate cancer risk, there is an accumulating weight of evidence consistently linking obesity to greater aggressiveness of disease. In probing this association mechanistically, it has been posited that peri‐prostatic adipose tissue (PPAT), a significant component of the prostate microenvironment, may be a critical source of fatty acids and other mitogens and thereby influences PCa pathogenesis and progression. Notably, several recent studies have identified secreted factors from both PPAT and PCa that potentially mediate the two‐way communication between these intimately linked tissues. In the present review, we summarize the available literature regarding the relationship between PPAT and PCa, including the potential biological mediators of that relationship, and explore emerging areas of interest for future research endeavours.